Level of Expressed Emotion Scale: Spanish validation for general adolescent population and development of a short version - Aguado, Verónica; Sorrel, Miguel Ángel; Corral, Susana; Martínez-Pampliega, Ana (Anales de Psicología / Annals of Psychology, 2024)
Expressed emotion is a construct that has so far been studied in a clinical population, although this work proposes its study in adolescent population without psychopathology. It has three aims: 1) To analyse the psychometric characteristics of the Level of Expressed Emotion Scale in the relationship of the Spanish adolescents with their father and their mother, considering different response format (dichotomic and polytomic); (2) To develop a short version of the scale; (3) To study the validity of the instrument as a measure of emotional climate of normative families. Participants were 827 adolescents from 12 to 17 years old. Data analysis included exploratory and confirmatory factor analysis and structural equation modelling. Results suggested a 4-factor structure in the short version composed by 16 items, with adequate psychometric properties. This is presented as an innovative and appropriate tool for the assessment of the emotional family climate, both for researchers and clinicians.